2009
DOI: 10.1088/0957-4484/20/45/455104
|View full text |Cite
|
Sign up to set email alerts
|

Gold and silver nanoparticles conjugated with heparin derivative possess anti-angiogenesis properties

Abstract: Silver and gold nanoparticles display unique physical and biological properties that have been extensively studied for biological and medical applications. Typically, gold and silver nanoparticles are prepared by chemical reductants that utilize excess toxic reactants, which need to be removed for biological purposes. We utilized a clean method involving a single synthetic step to prepare metal nanoparticles for evaluating potential effects on angiogenesis modulation. These nanoparticles were prepared by reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 36 publications
1
100
1
2
Order By: Relevance
“…Previous studies have shown that gold nanoparticles (AuNPs) can affect vascular endothelial growth factor (VEGF)-and basic fibroblast growth factor (bFGF)-induced cell proliferation in vitro and angiogenesis in vivo. 16,17 In addition, AuNPs bind to VEGF in arthritic synovial fluid, exert antiangiogenic activities, and reduce inflammation and arthritis. 18 However, some studies have also shown that nanoparticles, particularly high concentrations of silver nanoparticles, exhibit cell cytotoxicity and, therefore, induce HO-1 expression.…”
mentioning
confidence: 99%
“…Previous studies have shown that gold nanoparticles (AuNPs) can affect vascular endothelial growth factor (VEGF)-and basic fibroblast growth factor (bFGF)-induced cell proliferation in vitro and angiogenesis in vivo. 16,17 In addition, AuNPs bind to VEGF in arthritic synovial fluid, exert antiangiogenic activities, and reduce inflammation and arthritis. 18 However, some studies have also shown that nanoparticles, particularly high concentrations of silver nanoparticles, exhibit cell cytotoxicity and, therefore, induce HO-1 expression.…”
mentioning
confidence: 99%
“…34 Furthermore, addition of a sulfated oligosaccharide enhances angiogenesis and stabilizes the capillary network of new blood vessels. 10,35 Thus, a properly developed system of blood vessels of the correct diameter may decrease the resistance of peripheral vessels and, consequently, slightly decrease the force of heart contractions, leading to a proper heart weight. It should also be noted that the activity of alanine aminotransferase, aspartate aminotransferase, and other biochemical parameters of blood did not change, which otherwise could be the sign of distortion in the homeostasis of the organism, including the circulatory system.…”
Section: Discussionmentioning
confidence: 99%
“…9 The genetic capacity for proper development of muscle tissue in embryos of animals and humans may be hampered by a shortage of sulfur signaling compounds in the extracellular matrix, especially glycosaminoglycans. 10 The unique properties of gold nanoparticles (nano-Au) are due to their small size, much larger surface area per unit mass compared with larger particles, and a greater proportion of atoms exposed on the surface of the particles, making them much more reactive than larger particles. 11 Nano-Au exhibit a strong affinity for thiol groups, which allows efficient and selective bonding with intracellular compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The folate-conjugated heparin-taxol nanoparticles were more efficiently taken up by folate receptor overexpressing cancer cells compared with folate receptor-deficient cell lines. Heparin has also been conjugated with chitosan (47), gold (48), and iron oxide nanoparticles (49). Moreover, heparinbased co-polymers have been used to develop multifunctional nanoparticle systems for anti-cancer drug delivery.…”
Section: Nanoparticle Platforms: Emerging Translational Nanodrug Delimentioning
confidence: 99%